Propuesta de mejora para el sistema de tratamiento de agua potable del acueducto Veredal Coovesur Ltda. E.S.P. del municipio de Fusagasugá-Cundinamarca (2018)
The Coovesur potable water treatment plant of the Municipality of Fusagasugá-Cundinamarca, makes an average of 15 L / s of water from the Batán River drinkable. It has one intake, one sand trap, two landfills, two quick mix tanks, where Type A aluminum sulphate is applied, two settlers, three filtration equipment, disinfection using chlorine gas, three storage tanks, and a laboratory with 3 equipment. measurement. For each stage, a detailed diagnostic was made of each of the unit operations to determine the problem in each one of them. The physical - chemical and microbiological analyzes of raw and drinking water were taken, determining the parameters that did not comply or were outside resolution 2115 of 2007 (such as color, aluminum, microbiological, residual chlorine, total iron and pH), establishing the that present difficulties. The critical problem is the average concentration of aluminum 0.39 mg Al / L that historically exceeds the permitted limit for drinking water (0.2 mg Al / L), for this reason different jar tests were carried out where the dosages of the coagulant, the neutralizer, the disinfectant and the validation of a flocculant.